PENDIDIKAN PENGELOLAAN KEUANGAN KELUARGA, GAYA HIDUP, PEMBELAJARAN SERTA PENGARUHNYA TERHADAP LITERASI KEUANGAN - Atika Syuliswati (Akutansi Bisnis & Manajemen ( ABM ), 2020)
The purpose of this study was to examine the effect of family financial management education, life style, and learning in higher education to financial literacy simultaneously and partially to students of the Accounting Department of State Polytechnic Malang. This research is a quantitative research and a sample consist of 142 students of the Accounting Department of State Polytechnic Malang. The method used is survey method using questionnaire given to the respondent to be answered. Question in questionnaire using likert scale. Data analysis method used in this research is multiple linear regression analysis. The results showed simultaneously and partially family financial management education, life style, and learning in higher education have significant effect on financial literacy.